PERANAN AUDIT OPERASIONAL PADA UNIT KARYA PENDIDIKAN SEKOLAH DASAR ISLAM TERPADU ZAID BIN TSABIT KOTA BOGOR - Luthfi Hafizh Rizqullah; Amrul Khotibuziddan; Dharmawan Muhammad Irfan; Irman Suherman (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
The quality of primary and secondary education in Indonesia is still relatively low, due to the minimal fulfillment of basic and secondary education service standards, accompanied by rampant cases of corruption in the education sector. In an effort to improve school quality, it is necessary to have a routine evaluation program, one of which is through operational audits. The purpose of this study was to gain an in-depth understanding of the application of operational auditing in evaluating internal control at Zaid Bin Tsabit Integrated Islamic Elementary School, Bogor City. The audit is carried out through several stages, which in general can be grouped into three stages, namely: planning or preliminary survey, implementation and reporting. The implementation in the field resulted in audit findings which were weaknesses in operational activities at SDIT ZAID BIN TSABIT Bogor City. Then from the audit findings, development is carried out which aims to provide recommendations at the reporting stage so that management can make improvements. From the implementation of this operational audit, it is expected to improve the quality of education services at SDIT ZAID BIN TSABIT Bogor City, supported by transparency and accountability in the management of education services